Clinical Improvement in a Patient with Methanol-Induced Optic Neuropathy - Rusydiana; Aritonang, Christina; Agustini, Lukisiari (Vision Science and Eye Health Journal, 2025)
Introduction: Due to optic nerve and retinal damage, methanol-induced optic neuropathy (Me-ION) may lead to permanent vision loss, including blindness, making it a serious condition. Here, we present a case demonstrating clinical recovery in a patient with Me-ION. Case Presentation: A 20-year-old man came to the emergency unit with a chief complaint of sudden visual loss in both eyes since the day before admission. It was accompanied by shortness of breath, headache, nausea, and vomiting. He reported ingesting methanol three days before presentation and had no history of systemic illness. Visual acuity (VA) was counting fingers at one meter in the right eye and counting fingers at three meters in the left eye. The intraocular pressure (IOP) in both eyes was measured at 12.2 mmHg. Optical Coherence Tomography (OCT) of the retinal nerve fiber layer (RNFL) revealed increased thickness in both superior and inferior quadrants bilaterally. Laboratory tests revealed metabolic acidosis. The patient was diagnosed with Me-ION in both eyes, accompanied by metabolic acidosis. Dialysis was started, and he was treated with a high-dose steroid. Subsequently, VA improved to 5/5 in the right eye and 5/12 in the left eye. Color vision improved in the right eye to 30/38 (Ishihara), while the left eye remained at 20/38. Conclusions: Early diagnosis and prompt treatment of Me-ION can result in significant clinical improvement in visual acuity and color vision, emphasizing the significance of early treatment in managing toxic optic neuropathy.